(untitled) (American Journal of Islam and Society, 2011)
In the final decades of the twentieth century, a new strand of Islamic intellectualism began inserting itself into contemporary Muslim discourses on politics, law, and human rights. Not fitting into existing neat categories such as traditionalist, revivalist, and modernist-liberal Islam, its promoters operate on the interstices of established traditions and practices within the Muslim world, as well as the liminal spaces between cultures and civilizations. With the advent of the new millennium, the impact of their alternative, cosmopolitan or culturally hybrid ways of engaging with the Islamic heritage, or turath, is receiving increasing recognition. In his latest book, Religion and Politics in the Middle East, which examines whether religion has primacy over politics or the other way around, Robert D. Lee’s focus has shifted from individuals (Muhammad Iqbal, Sayyid Qutb, Ali Shariati, and Mohammed Arkoun) to a quartet of countries (Egypt, Israel, Turkey, and Iran). At the same time, he continues to acknowledge the significance of maverick thinkers such as the Egyptian Nasr Hamid Abu Zayd, Turkey’s Said Nursi and Fethullah Gülen, and the Iranian Abdolkarim Soroush and Mohsen Kadivar in questioning, challenging, and transforming the intellectual and political scenes in their respective countries and beyond—although often forced to do so from abroad as exilic intellectuals ...